Trachyonychia successfully treated with low-dose acitretin in a paediatric patient - Siekierko, Aleksandra; Sadowska, Magdalena; Niedźwiedź, Michał; Kijowska, Karolina; Żak, Magdalena; Skibińska, Małgorzata; Lesiak, Aleksandra; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Trachyonychia is a rare disorder of the nail unit in which surface of the nails is rough like sandpaper or glossy with pits. It is mostly idiopathic but can also be associated with other diseases. Diagnosis is based mainly on the clinical picture as histopathology is not routinely evaluated. Treatment of the condition is challenging and usually disappointing [1, 2]. We report a case of trachyonychia successfully treated with acitretin in a paediatric patient.